A CONCEPT FOR INCLUSIVE PHYSICAL EDUCATION TRAINING PROGRAM FOR FUTURE PRE-SCHOOL AND PRIMARY-SCHOOL TEACHERS - G. Terzieva (Trakia Journal of Sciences)
The adoption of new normative documents in the field of education in Bulgaria determines the inclusion of children with special educational needs in general education schools. The significant and integral role which physical education plays in the educational process poses the question of the inclusion of children with impairments in motor activity training as well. Teachers implementing it contribute greatly to its positive effects. The main features of physical education include active motor activity and the related physical workload. In order for them to be adapted successfully to the specific needs of children with different disabilities, more specialized training is required. The analysis of the curricula of the faculties of education in Bulgaria shows that future pre-school and primary school teachers who will be responsible for the physical education of children in kindergartens and primary schools respectively do not receive appropriate training in adaptive physical education. The aim of this article is to present a concept for introducing a training program on "Motor Activity Training and Inclusive Physical Education", intended for students of the specialty Preschool and Primary School Education at the Faculty of Education, Thrakia University, Bulgaria.